Analisis Klausa pada Novel Argantara Karya Falistiyana Berdasarkan Makna Unsur-Unsurnya - Anelia Histi Harianja; Sarma Panggabean; Intan Galingging (ESTETIK : Jurnal Bahasa Indonesia, 2022)
The purpose of this study was to find clauses based on meaning and to find out the language of the novel's contents. The research method used is descriptive analysis method. From the analysis carried out, there are groups of clauses in each data found in the novel Argantara. In that clause there is the meaning of Filling Element P, Filling Element P states Condition, Filling Element P stating the meaning of 'Existence', Filling Element P stating the meaning of 'Existence', Filling Element P stating the meaning of 'Identifier', Element P stating the meaning of 'amount', Elements filler S states the meaning of 'actors', filler S states the meaning of 'tools', filler element S states the meaning of 'suffering', filler element S states the meaning of 'place', filler element S expresses the meaning of â€œknownâ€ Filler element O1 states the meaning of 'tools', filler elements O1 states the meaning of 'receiver'', the filler element O2 states the meaning of 'patient', the filler element O2 states the meaning of 'result'. The results of this study are useful for students, especially for students because it provides insight into the clauses and examples of each clause sentence in the novel.